Correlation Between The Knowledge Level About Eating Patterns And The Incidence Of Anemia In Adolescents During Covid-19 Pandemic - Anik Sulistiyanti; Fany Dwi Yulianti; Yulia Nur Khayati (Proceeding of International Conference on Science, Health, And Technology, 2021)
The World Health Organization (WHO) determined that on March 12, 2020, it would receive a threat as a world pandemic status due to Coronavirus Disease (Covid-19). Coronavirus Disease (Covid-19) has an impact on all structures of life, which is felt by adolescents, especially those whose lives are in difficult and / or disadvantaged conditions. Covid-19 has the potential to transmit the virus to other people, and in some cases teenagers have to be isolated in hospital because of serious conditions. Changes in the covid-19 pandemic can affect knowledge, psychosocial and consumption patterns of adolescents so that it can cause anemia. Anemia is a condition in which the hemoglobin level is below 12g%. The purpose of this study was to determine correlation between the knowledge level about eating patterns and the incidence of anemia in adolescents during Covid-19 pandemic. This type of research analytic observational study with a cross sectional study design. The study population was all adolescents in SMA N 3 Sragen. The research sample was 60 adolescents with proportional random sampling technique. Data collection using examination of haemoglobin levels and a closed questionnaire. Data analysis with univariate analysis and bivariate analysis using chi square statistical test. The results showed that the level of knowledge of adolescents about eating patterns was mostly respondents with the less category, namely as many as 33 respondents (55%). The result shows that the incidence of anemia is mostly respondents with anemia category as many as 36 respondents (60%). The results of the statistical tests with chi-square obtained value = 17.911> 5.59 and p value = 0.000 <0.05 then Ho is rejected and Ha is accepted, which means statistically it can be concluded that there is a correlation between the level of adolescent knowledge about eating patterns with anemia in students of SMAN 3 Sragen. the result is 0.479 so that the close correlation between the level of knowledge of adolescents about eating patterns and the incidence of anemia is moderate. There is a correlation between the knowledge level about eating patterns and the incidence of anemia in adolescents during Covid-19 pandemic